İzzet Efendi, One Of The 18th Century Poets And His Biladiyye - Kaplan, Yunus (Fırat University, 2021)
The biladiyyes (literal works discussing the cities) as a literal type are the poems that a great of them is written about the settlements in Ottoman geography. Generally, the name of places was mentioned as a name with some literal arts and meaning recalls in this type of poem that the classification of settlements were not made. The most famous one among the biladiyyes that nearly ten samples have been available in the classical Turkish literature up to now belongs to Arayıcızade Hüseyin Ferdi who was one of 17th century’s poets. Mrs. Derviş Ömer, Fasîhî, Zihnî, Mrs. İştibî Ahmed, Mecdî, Lutfî and Priştineli Vâsık are ones of the poets having such kind of works, except from Ferdi. One of those preferring this type is Mrs. İzzet of divan poets of 18th century. The poet mentioned the names of nearly 200 places in his biladiyye which consisted of 102 couplets. The work has an originality in terms of its capacity and the number of places’ mentioned names. In this research, the information was given about Mrs. İzzet’s life, the translated text was presented after the biladiyye’s form and content features were considered.

Edebî bir tür olarak bilâdiyyeler, büyük çoğunluğu Osmanlı coğrafyasındaki yerleşim yerleri hakkında kaleme alınan manzumelerdir. Genellikle yerleşim yerlerinin tavsifinin yapılmadığı bu türdeki manzumelerde, yer isimleri bazı edebî sanatlar ve anlam çağrışımlarıyla birlikte ismen zikredilmiştir. Klasik Türk edebiyatında şimdilik on civarında örneği bulunan bilâdiyyeler içinde en meşhuru 17. yüzyıl şairlerinden Arayıcızâde Hüseyin Ferdî’ye aittir. Ferdî dışında Derviş Ömer Efendi, Fasîhî, Zihnî, İştibî Ahmed Efendi, Mecdî, Lutfî ve Priştineli Vâsık da bu türde eser sahibi olan şairlerdir.Bu türü tercih edenlerden biri de 18. yüzyıl divan şairlerinden İzzet Efendi’dir. Şair, 102 beyitten müteşekkil olan bilâdiyyesinde 200 civarında yer ismini zikretmiştir. Eser, bu hâliyle hem sahip olduğu hacim hem de zikredilen yer isimlerinin sayısı açısından özgünlük arz etmektedir. Bu çalışmada İzzet Efendi’nin hayatı hakkında bilgi verilmiş, bilâdiyyesinin şekil ve muhteva özellikleri üzerinde durulduktan sonra çeviriyazılı metni sunulmuştur.
18. YÜZYIL ŞAİRLERİNDEN İZZET EFENDİ VE BİLÂDİYYESİ